(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Purpose: To examine the features of the bulbar conjunctiva in patients who developed dry-eye disease (DED) after drug treatment for primary open-angle glaucoma (POAG). Methods: Impression cytology was performed by applying twice a strip of cellulose acetate filter to the ocular surface to remove the superficial epithelial layers of the temporal bulbar conjunctiva. The strips were removed with a peeling motion in a few seconds, and the samples were immediately fixed in 95% ethyl alcohol, stained with hematoxylin and eosin, mounted on glass slides and coverslipped for light microscopy. Squamous metaplasia was graded according to Nelson’s grading system on the basis of cell morphology, staining and integrity as well as the nucleus-to-cytoplasm ratio. This study included a case group of 80 patients (mean age, 63.8 ± 6.7 years) with POAG-associated DED, with the group being divided into four subgroups. Subgroups 1 and 2 were composed of 40 patients each, with glaucoma duration of less or more than 5 years, respectively. Subgroups a and b were composed of 40 patients each, with a number of topical ocular hypotensive drugs used equal to one or at least two, respectively. The control group was composed of 20 apparently healthy volunteers (mean age, 67.9 ± 8.9 years). All patients underwent a routine eye examination. Results: All patients with glaucoma had symptoms of DED with Ocular Surface Disease Index (OSDI) scores of at least 15. In subgroup 1, 60% had Nelson’s grade 1 and 40%, Nelson’s grade 2 squamous metaplasia. In subgroup 2, 10% had Nelson’s grade 1; 60%, Nelson’s grade 2 and 30%, Nelson’s grade 3 squamous metaplasia. In subgroup a, 20% had Nelson’s grade 1; 60%, Nelson’s grade 2 and 30%, Nelson’s grade 3 squamous metaplasia. In subgroup b, 10% had Nelson’s grade 1; 60%, Nelson’s grade 2 and 30%, Nelson’s grade 3 squamous metaplasia. Conclusion: Changes in the bulbar conjunctival epithelium corresponded to Nelson’s grade 2 or 3 squamous metaplasia in 80% of patients who developed DED after drug treatment for POAG. The severity of squamous metaplasia correlated with the duration of glaucoma and, consequently, longer use of hypotensive eye drops (r1 = 0.15, p1 = 0.02, p2 = 0.01). Findings of the current study and international guidelines argue for the use of the medications containing no preservatives or potentially toxic components in long-term therapy against glaucoma.